2021
DOI: 10.3390/cryst11121455
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Curing Conditions on the Strength Development of Alkali-Activated Mortar

Abstract: In this study, the strength development and microstructure evolution of alkali-activated fly ash (AAF), granulated blast furnace slag (AAG), and metakaolin (AAM) mortars under standard curing, steam curing, and oven curing conditions were investigated. The results show that 80 °C steam curing was more suitable for AAF mortar. Although oven curing was not as good as steam curing under the same temperature, the water evaporation increased the volume density of the N-A-S-H gel and refined the pore structure. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The silica content (SiO2) and the alumina content (Al2O3) represents approximately 80 -95% of the fly ash content [29], and plays a major role in produced GPC mix properties [30][31][32]. Similarly, the type of alkaline activator , and curing conditions [36,37] would affect the strength and durability of hardened geopolymers.…”
Section: Fly Ash Pozzolanic Activitymentioning
confidence: 99%
“…The silica content (SiO2) and the alumina content (Al2O3) represents approximately 80 -95% of the fly ash content [29], and plays a major role in produced GPC mix properties [30][31][32]. Similarly, the type of alkaline activator , and curing conditions [36,37] would affect the strength and durability of hardened geopolymers.…”
Section: Fly Ash Pozzolanic Activitymentioning
confidence: 99%
“…The largest application may be for airport runway materials in Australia [ 11 ]. Alkali-activated materials produced by steam curing and autoclaved curing, which are generally applied to conventional precast concrete products, were also studied; it was reported that rapid strength development is possible by these high-temperature curing methods [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…RCP from waste cement mortars is mainly composed of silicon and aluminum compounds, such as SiO 2 and Al 2 O 3 , which have potential alkali activity. Hence, granulated blast furnace slag (GBFS), fly ash (FA) and AARCPC can be synthesized to geopolymers [17][18][19][20][21][22] by regulating the compounds, fineness and activation technology. However, RCP has low pozzolanic activity and is composed of irregular particles, which limits its use in cement-based materials.…”
Section: Introductionmentioning
confidence: 99%